2016
DOI: 10.7717/peerj.1655
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of structural relationship among achievement motive on social participation, purpose in life, and role expectations among community dwelling elderly attending day services

Abstract: Background. Achievement motive is defined as the intention to achieve one’s goals. Achievement motive is assumed to promote clients to choices and actions toward their valuable goal, so it is an important consideration in rehabilitation.Purpose. The purpose of this study is to demonstrate the structural relationship among achievement motive on purpose in life, social participation, and role expectation of community-dwelling elderly people.Methods. Participants were community-dwelling elderly people in day-serv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 26 publications
1
27
0
7
Order By: Relevance
“…5,7) The SAMR is a self-report questionnaire that focuses on activities unique to rehabilitation; it has a two-factor structure: (1) self-masteryderived achievement motive and (2) means/process-oriented achievement motive. Self-mastery-derived motive refers to making an effort to enhance one's own abilities and intel-ligence; means/process-oriented motive emphasizes the willingness to follow a rehabilitation program to achieve one's goals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,7) The SAMR is a self-report questionnaire that focuses on activities unique to rehabilitation; it has a two-factor structure: (1) self-masteryderived achievement motive and (2) means/process-oriented achievement motive. Self-mastery-derived motive refers to making an effort to enhance one's own abilities and intel-ligence; means/process-oriented motive emphasizes the willingness to follow a rehabilitation program to achieve one's goals.…”
Section: Introductionmentioning
confidence: 99%
“…5) In previous studies, achievement motive has been shown to affect various outcomes such as healthrelated quality of life, purpose in life, social participation, and self-efficacy. [7][8][9] However, few studies have sought to identify factors that can influence achievement motive. Consequently, the possibilities for effective intervention in this regard remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in rehabilitation have shown that achievement motive has a positive correlation with health-related quality of life (HRQOL), and achievement motive has been indicated to further develop HRQOL by promotion of social participation . In addition, achievement motive has been shown to have a positive impact on purpose in life and role expectation (Sano & Kyougoku 2016), and is expected to play an important role in community-based rehabilitation that focuses on ''Activity'' and ''Participation,'' according to the International Classification of Functioning, Disability, and Health framework (Tsuruta 2015).…”
Section: Introductionmentioning
confidence: 99%
“…International University (No. [17][18][19][20][21][22]. The participants had the right to withdraw from the study at any time for any reason.…”
Section: Ethics Statementmentioning
confidence: 99%